Characteristics Finite Element Methods in Computational Fluid Dynamics - Iannelli, Joe (Computational Fluid and Solid Mechanics, 2006)
This book details a systematic characteristics-based finite element procedure to investigate incompressible, free-surface and compressible flows. The fluid dynamics equations are derived from basic thermo-mechanical principles and the multi-dimensional and infinite-directional upstream procedure is developed by combining a finite element discretization of a characteristics-bias system with an implicit Runge-Kutta time integration. For the computational solution of the Euler and Navier Stokes equations, the procedure relies on the mathematics and physics of multi-dimensional characteristics. As a result, the procedure crisply captures contact discontinuities, normal as well as oblique shocks, and generates essentially non-oscillatory solutions for incompressible, subsonic, transonic, supersonic, and hypersonic inviscid and viscous flows.